Case report: Effectiveness of low-dose methotrexate monotherapy in post-essential thrombocythemia myelofibrosis - Francis, Sebastian; King, Tom; Zeidler, Martin P. (Frontiers in Medicine, 2024)
JAK/STAT pathway signalling is associated with both chronic inflammatory conditions such as psoriasis and haematological malignancies such as the myeloproliferative neoplasms (MPNs). Here we describe a 73yo female patient with a history of chronic plaque psoriasis, post-essential thrombocythemia myelofibrosis (MF) and a quality of life substantially impacted by both conditions. We report that 15mg oral Methotrexate (MTX) weekly as a monotherapy is well tolerated, provides a substantial clinical improvement for both conditions and significantly improves quality of life. We suggest that the recently identified mechanism of action of MTX as a JAK inhibitor is likely to explain this efficacy and suggest that repurposing MTX for MPNs may represent a clinical-and cost-effective therapeutic option.JAK/STAT pathway signalling is central to multiple biological processes including inflammation, haematopoiesis and regulation of the immune system (1). Ectopic pathway activation is also associated with both chronic inflammatory conditions such as rheumatoid arthritis and psoriasis, as well as the chronic myeloid cancers collectively termed myeloproliferative neoplasms (MPNs) (2). MPNs include essential thrombocythemia (ET), associated with increased platelet counts, polycythemia vera (PV) associated with increased erythrocytes and myelofibrosis where bone marrow is replaced by fibrotic scar tissue -a condition that can be both a primary disease and a secondary development following ET or PV. In all cases, MPNs are associated with increased JAK/STAT pathway activity driven by gain-of-function mutations such as JAK2 V617F, indel mutations resulting in a +1 frameshift affecting the C-terminal of Calreticulin or activating mutations adjacent to the transmembrane region of the thrombopoietin receptor MPL W515L/K (reviewed in (2)).Given the pathological role of JAK/STAT signalling in both inflammatory diseases and MPNs, pathway inhibitors targeting JAK tyrosine kinases have been developed and deployed to the clinic (3, 4). In inflammatory diseases kinase inhibitors such as Tofacitinib (JAK1/2),